Organoboron Complexes as Thermally Activated Delayed Fluorescence (TADF) Materials for Organic Light-Emitting Diodes (OLEDs): A Computational Study - Jamilah A. Asiri; Walid M. I. Hasan; Abdesslem Jedidi; Shaaban A. Elroby; Saadullah G. Aziz; Osman I. Osman (Molecules, 2023)
We report on organoboron complexes characterized by very small energy gaps (ΔEST) between their singlet and triplet states, which allow for highly efficient harvesting of triplet excitons into singlet states for working as thermally activated delayed fluorescence (TADF) devices. Energy gaps ranging between 0.01 and 0.06 eV with dihedral angles of ca. 90° were registered. The spin–orbit couplings between the lowest excited S1 and T1 states yielded reversed intersystem crossing rate constants (KRISC) of an average of 105 s−1. This setup accomplished radiative decay rates of ca. 106 s−1, indicating highly potent electroluminescent devices, and hence, being suitable for application as organic light-emitting diodes.